2014
DOI: 10.1159/000355719
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Hemolysis, Vascular Endothelial Cell Activation and Thrombophilia in Splenectomized Patients with Hemoglobin E/β-Thalassemia Disease

Abstract: The relationship between asplenia and thrombophilia in β-thalassemia disease patients is not yet completely understood. One hundred and ten adult hemoglobin (Hb) E/β-thalassemia (E/β-Thal) disease outpatients, dichotomized according to the presence or absence of the spleen, were prospectively studied for evidence of intravascular hemolysis (IVH) and vascular endothelial cell (EC) activation. Biomarkers of IVH (serum cell-free Hb), EC [soluble E-selectin (sE-selectin) and soluble vascular cell adhesion molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…As such, the report by Atichartakarn et al [5], in association with others [6,7], provides data to indicate that splenectomy in thalassemia and HS, respectively, may have important pathophysiological consequences related to the induction, or prevention, of IVH, respectively (fig. 1).…”
Section: Figmentioning
confidence: 85%
See 3 more Smart Citations
“…As such, the report by Atichartakarn et al [5], in association with others [6,7], provides data to indicate that splenectomy in thalassemia and HS, respectively, may have important pathophysiological consequences related to the induction, or prevention, of IVH, respectively (fig. 1).…”
Section: Figmentioning
confidence: 85%
“…A number of risks and complications are reported to be associated with splenectomy, including an increased risk of infection and venous thromboembolism [1,4]. In this issue of Acta Haematologica, Atichartakarn et al [5 ]report important data to indicate that, following splenectomy, hemoglobin E/β-thalassemia individuals present a significant increase in IVH (as indicated by elevated circulating levels of cell-free hemoglobin), in association with alterations in markers consistent with inflammation, endothelial activation and hypercoagulability. Authors suggest that such IVH could participate in the thrombophilia that has been observed in postsplenectomized thalassemia.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…A splenectomy is performed to reduce the risk of spleen-induced extravascular hemolysis in patients exhibiting signs of hypersplenism, which increases blood transfusion requirements (9). A previous study reported increased levels of serum cell-free Hb, which provides evidence of intravascular hemolysis (10). …”
Section: Introductionmentioning
confidence: 82%